Rancang Bangun Sistem Informasi Perlengkapan Laboratorium Komputer Berbasis Web - Asep Saifudin; Gustina Gustina (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2021)
Computer Laboratory Equipment that runs on PPM Al Hasyimiyah Cilegon City uses manual starting from recording incoming goods and goods, recording outgoing goods inventory, checking goods, to producing inventory reports. To help with this problem, a computer laboratory equipment inventory information system is needed, the SWOT analysis method, sublime text software, uml using the visual paradigm, MySQL as a database which will make it easier for the admin to record goods data, incoming goods inventory, outgoing goods inventory, checking goods and make a report.